Handbook on teaching social issues - Evans, Ronald W. (Charlotte, NC : INFORMATION AGE PUBLISHING, INC., 2021)
"The Handbook on Teaching Social Issues, 2nd edition provides teachers and teacher educators with a comprehensive guide to teaching social issues in the classroom. This second edition frames the teaching of social issues with a strong emphasis on issues of social justice. It raises the potential for a new and stronger focus on social issues instruction in schools. Contributors include many of the leading experts in the field of social studies education. The volume includes 31 chapters and 7 sections including (1) Re-Framing the Teaching of Social Issues, (2) Critical Social Issues in the Curriculum, (3) In a Disciplinary Vein: Social Issues in the Subject Areas, (4) You Do Issues and Inquiry with Kids? Social Issues and Inquiry Learning in Elementary Schools, (5) The Heavy Topics: Human Rights, Genocide, Sustainability, (6) On Why and How: Methods for Teaching Social Issues, (7) The Latest and Best Resources and Materials"--
Revised edition of Handbook on teaching social issues, [1996]
Includes bibliographical references.
Keywords: Social sciences -- Study and teaching -- United States; Social problems -- Study and teaching -- United States; Social policy -- Study and teaching -- United States; United States -- Social conditions -- Study and teaching